The Association of Sleep Disturbances With Quality of Life in Heart Failure Patient–Caregiver Dyads. (April 2017) - Al-Rawashdeh, Sami Y.; Lennie, Terry A.; Chung, Misook L.
Sleep disturbance is common in patients with heart failure and their family caregivers. The purpose of this study was to determine whether sleep disturbances of patients and their spousal caregivers predicted their own and their partners' quality of life (QoL) in 78 heart failure patient–spousal caregiver dyads. Sleep disturbance was assessed using a composite score of four common sleep complaints. QoL was assessed by the physical and mental well-being subscales of the Short-Form 12 Health Survey. The multilevel dyadic actor–partner interdependence model analysis was used to determine the association between sleep disturbance and QoL. Each individual's sleep disturbance predicted their own poor physical and mental well-being while spousal caregivers' sleep disturbance predicted their partners' mental well-being. Results indicated that patients' mental well-being is sensitive to their spouses' sleep disturbance. Interventions targeting improving sleep and QoL may have to include both patients and spousal caregivers.